The Level of Knowledge About Health and Dental Care in Non-Dental Medicine Students - Ramadhan, Naufal Thufail; Sari, Annisa Fitria; Prakoso, Moch. Reyhan Tri; Dinda Nindy Oktaviany, Dinda Nindy; Aula, Achmad Chasina; Kusumo, Aryo Dwipo (International Journal of Psychosocial Rehabilitation, 2020)
Background: Knowledge is a factor influencing one's hygiene. Dental and oral health can be supported by the awareness to maintain and prevent problems with the treatment of oral and teeth. Objective: This study aims to determine the level of student knowledge about health and dental and oral care. Method: This research was descriptive research using the questionnaire method. Sampling was obtained by random sampling with a sample of 97 people. Results: The results showed that as many as 89.5% of female respondents and 92.3% of male respondents had a high level of knowledge about oral health. As many as 80.7% of female respondents and 84.6% of male respondents had a high level of knowledge about dental and oral care. As many as 100.0% of respondents from the health faculties and 88.6% of respondents from the non-health faculties had a high level of knowledge about dental and oral health. As many as 84.6% of respondents from the health faculty and 81.4% of respondents from the non-health faculty had a high level of knowledge about dental and oral care. Conclusion: The level of knowledge about health and dental and oral care was found higher in males than females, as well as in respondents from the health faculties compared to the non-health faculties.